Lateral approach of exploratory laparotomy through the open chest wall injury - Jonghwan Moon; Byung Hee Kang (Trauma Case Reports, 2018)
A combined laparotomy and thoracotomy is required in a few trauma patients. The anterior approach is a standard procedure used in such cases; however, a different approach may be required. Recently, we managed a patient who presented with a crush injury to the left side of his chest with associated bowel herniation. We performed the operation with the lateral approach, and even the laparotomy was performed though the rupture wound in the diaphragm. The operation could be successfully completed without changing the patient's position or creating an additional incision. Although the patient recovered well postoperatively, lateral approach for laparotomy had some limitations. Keywords: Wounds and injuries, Laparotomy, Diaphragm, Thorax